MECHANICAL ENGINEERING ENTERPRISES IN MODERN CONDITIONS AND THEIR SIGNIFICANCE IN THE SYSTEM OF ECONOMIC SECURITY - Zasanskyi, Volodymyr; Saponenko, Yurii (Social Development: Economic and Legal Issues, 2026)
At the current stage of economic development, in conditions of prolonged and exhausting military confrontation, the domestic machine-building sector demonstrates a sharp polarization: on the one hand, civilian enterprises are forced to adapt to the complications and obstacles of activity, and on the other hand, crisis conditions stimulate rapid growth, modernization and relocation of enterprises integrated into the defense-industrial complex and the production of dual-use products. The study is devoted to the analysis of the state of modern security management of machine-building enterprises. All data used for the study were obtained from open sources and were subjected to critical analysis. The article substantiated that the support of sustainable economic development in wartime is ensured by an appropriate level of competitiveness and security. In this regard, the issues of building a system for managing the economic security of this sector are of paramount importance. The study found that ensuring the security of the system and its safety as a fundamental characteristic is a direct consequence of effective management, building a security culture and implementing specific functions (in particular, security and detective practice). The effectiveness of these processes is determined by both the internal parameters of the security system (human resource competence, technical and legal basis) and the general level of development of the socio-economic environment. It is substantiated that the synthesis of these factors provides the economic system with stability and autonomy, thanks to which the enterprise acquires the ability not only to eliminate threats, but also to form a reliable basis for protecting corporate interests, stable development and preserving its structural integrity. It is this set of tasks that determines the essence of security and the functionality of specialized entities.